2015
DOI: 10.1371/journal.pone.0135481
|View full text |Cite
|
Sign up to set email alerts
|

CRP-Mediated Carbon Catabolite Regulation of Yersinia pestis Biofilm Formation Is Enhanced by the Carbon Storage Regulator Protein, CsrA

Abstract: The natural transmission of Yersinia pestis is reliant upon biofilm blockage of the flea vector. However, the environmentally-responsive adaptive regulators which facilitate Y. pestis biofilm production in accordance with the flea midgut milieu are not well understood. We seek to establish the impact of available carbon source metabolism and storage upon Y. pestis biofilm production. Our findings demonstrate that Y. pestis biofilm production is subject to carbon catabolite regulation in which the presence of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 45 publications
(73 reference statements)
3
36
0
2
Order By: Relevance
“…In Yersinia spp., in addition to regulation of pla, Crp regulates expression of genes encoding the type III secretion system and its effectors (19), the anti-phagocytic capsule F1, and hundreds of other protein-coding genes and small noncoding RNAs (sRNAs) (20,21). In addition, Crp has been suggested to regulate biofilm formation in Y. pestis indirectly and with CsrA (22,23). In contrast to expression in Escherichia coli, expression of crp itself in Y. pestis is not directly auto-regulated (24,25) but is regulated by the PhoP response regulator (26).…”
mentioning
confidence: 99%
“…In Yersinia spp., in addition to regulation of pla, Crp regulates expression of genes encoding the type III secretion system and its effectors (19), the anti-phagocytic capsule F1, and hundreds of other protein-coding genes and small noncoding RNAs (sRNAs) (20,21). In addition, Crp has been suggested to regulate biofilm formation in Y. pestis indirectly and with CsrA (22,23). In contrast to expression in Escherichia coli, expression of crp itself in Y. pestis is not directly auto-regulated (24,25) but is regulated by the PhoP response regulator (26).…”
mentioning
confidence: 99%
“…These data more likely suggest genes for regulating biofilm formation are controlled by environmental factors, such as temperature and growth in the flea (41,42). Carbon source is also known to play a role (13), and while we observed no difference in expression of the diguanylate cyclases in biofilms, they were significantly upregulated in glycerol compared to glucose (Dataset 1).…”
Section: Global Analysis Of Gene Expressionmentioning
confidence: 68%
“…While known for its role during catabolite repression and regulation of the lac operon, it is now appreciated that Crp regulates expression of other genes, including factors important during infection to connect changes in glucose availability to regulation of bacterial behaviors. Across γ-proteobacteria, Crp regulates biofilm formation (12,13), capsule production (14), the DNA damage response (15), toxin production (16,17), luminescence (18), and iron acquisition (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A microarray analysis further demonstrated that multiple genes of the virulence plasmid associated Ysc type III secretion system are differentially expressed in a csrA mutant of Y. pseudotuberculosis [13]. Furthermore, the Csr system is implicated in the control of biofilm formation, resistance against antibiotic, osmotic, and heat stress, as well as numerous metabolic pathways [11,13,14]. A major feature is that CsrA adjusts the central carbon flow through the pyruvate-acetate node and the tricarboxylic acid cycle in response to nutrient availability [13].…”
Section: Trans-acting Rnas Of Yersiniamentioning
confidence: 99%